Reservoir characterization of the Upper Triassic Snadd Formation in the southwestern Barents Sea - Marcilly, Chloe Franca Margot (2016)
The Barents Sea is the new target area for the oil industry, particularly the Triassic and Jurassic strata. Deeply buried sandstone reservoirs have proved to have good quality in the North Sea due to presence of chlorite coating. The aim of this study is to investigate the processes and factors influencing the reservoir quality of the Late Triassic Snadd Formation in the southwestern Barents Sea. The Snadd Formation includes a large range of depositional environments and this study highlights their impact on the reservoir quality by comparing between datasets from the Hammerfest Basin and the Bjarmeland Platform. This thesis is part of the project Trias North reconstructing the Triassic Barents shelf. Core material and well data from two wells were examined using sedimentological and petrographical as well as petrophysical approach. The sedimentological and petrographical analyses are composed of core logging, optical and scanning electron microscopy (SEM) associated with X-ray diffraction. Wireline logs were used to make the petrophysical analysis. Both studied locations show poor reservoir potential for oil due to the low porosity resulting from high compaction and abundant clay minerals from deposition and infiltration. Those clay minerals greatly participate to the reduction of the porosity and permeability due to burial diagenesis processes such as illitisation and quartz cement. The thick sandstone deposits of the Bjarmeland Platform, even if the overall porosity is close to the 10% cut off, can still represent a good reservoir for gas production. The potential stacking of the fluvial channel deposits may reinforce the value of the reservoir. This study proves that the initial composition of the deposits, as well as their depositional environments, is decisive for the reservoir quality as they govern the diagenetic processes controlling it. Some particular features proper to each well such as the presence of dolomite and sphaerosiderites have been investigated in view to qualify their influence on the local reservoir quality.